Pengembangan Bahan Ajar “Nilai Karakter Tokoh Pandawa” untuk Sekolah Dasar - Catur Arib Akbar Arrofiif; Retno Winarni; Joko Daryanto (Didaktika Dwija Indria, 2026)
This study aims to identify the characteristics of teaching materials needed inlearning Javanese, develop and produce teaching materials "Character Values of PandawaFigures" for Elementary Schools, and analyze their feasibility. The method used is researchand development with the ADDIE model. Data were obtained through observation, interviews,needs questionnaires, and assessment questionnaires from material experts, media experts,practitioners, and art experts. The results of the study include analysis of teaching materialneeds, development process, final product in the form of textbooks, and feasibility test results.The conclusion shows that the teaching materials needed are simple textbooks, easy tounderstand, independent, focused on Pandawa character values, and do not require additionalmaterials. The development follows the ADDIE model, and the results are textbooks that are inaccordance with the needs of educators. The validity of the teaching materials scored 84%from material experts (valid), 90% from media experts (very valid), 75% from practitioners(valid), and 80% from art experts (valid).